Effect of spacing and seedling age on yield, quality and heat use of scented rice in lower gangetic plains of West Bengal - Bera, Shilpi; Ghosh, Mrityunjay; Banerjee, S; Mondal, S; Nanda, MK (ORYZA-An International Journal of Rice, 2021)
A traditional scented rice (cv. Radhunipagal) was tested under varied spacing (20 cm × 20 cm, 20 cm × 15 cm, 15 cm × 15 cm and 20 cm × 10 cm) and seedling age (25, 35 and 45 days) during wet (kharif) season of 2018 at B.C.K.V., Nadia, West Bengal. Seedling age caused significant variation in life duration and summed GDD from 147.9 days and 2436°C day (25-day aged) to 162.0 days and 2753°C day (45-day aged), but with maturity in same meteorological week. Square planting (15 cm × 15 cm or 44 hills m-2) resulted in highest grain yield (2.52 t ha-1), which was 2.85, 11.01 and 4.56% greater over wider (20 cm × 15 cm and 20 cm × 20 cm) and closer spacings (20 cm × 10 cm). Radhunipagal rice raised with 25-days old seedlings recorded the highest grain yield (2.53 t ha-1) and maximum heat use efficiency (0.90 kg ha-1 °C day-1), and that yield was 0.12 and 0.22 t ha-1 greater over the crops planted with 35 and 45-days old seedlings during wet season. Spacing could not influence the cooking and processing quality (gelatinization temperature, kernel elongation ratio and aroma) except protein content of milled rice in the study. Radhunipagal paddy planted with 45-day aged seedlings recorded maximum protein content (6.36%) and alkali spreading value (score 3.27).